2018
DOI: 10.1186/s13561-018-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review about costing methodology in robotic surgery: evidence for low quality in most of the studies

Abstract: ObjectivesThe main objective of this review was to evaluate the methodological design in studies reporting resource use and costs related to robotic surgery in gynecology.MethodsSystematic searches were performed in the databases PubMed, Embase, Scopus, and The Centre for Reviews and Dissemination database for relevant studies before May 2016. The quality of the methodological design was assessed with items regarding methodology from the Consolidated Health Economic Evaluation Reporting Standards (CHEERS). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The robotic platform has been rapidly adopted for gynecological procedures in the US and Europe thereby reducing the use of Open Access Surgery (OAS) [1]. The establishment of robotic surgical availability is associated with high initial purchase costs of the platform and additional maintenance and surgical supply costs [2,3]. In a recent review, we compared the methodological design in 32 cost studies within the gynecological field [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The robotic platform has been rapidly adopted for gynecological procedures in the US and Europe thereby reducing the use of Open Access Surgery (OAS) [1]. The establishment of robotic surgical availability is associated with high initial purchase costs of the platform and additional maintenance and surgical supply costs [2,3]. In a recent review, we compared the methodological design in 32 cost studies within the gynecological field [2].…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of robotic surgical availability is associated with high initial purchase costs of the platform and additional maintenance and surgical supply costs [2,3]. In a recent review, we compared the methodological design in 32 cost studies within the gynecological field [2]. Most studies suffered from selection bias, as they were not able to control for data on tumor stage, comorbidities and/or unobservable patient characteristics [2,[4][5][6][7][8], nor did they control for prior levels of health care service use.…”
Section: Introductionmentioning
confidence: 99%
“…The cost-effectiveness plane and WTP are demonstrated in Figure 7. Recently a systematic review of costing methodology in robotic surgery in gynaecology revealed a lack of high-quality trials reporting on resource use and costs (Korsholm, et al 2018). To obtain a more comprehensive understanding of the effects and costs, it seemed essential to include and evaluate a cost-effectiveness analysis, with QALY as an outcome measure, in our study about robotic hysterectomy compared with abdominal hysterectomy for treating early endometrial cancer in an ERAS programme.…”
Section: Health Economics and Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…Further, hospitals use a variety of approaches to robotic cost accounting, making it difficult, if not impossible, to determine accurate CoO assessments within a hospital and across hospitals. A recently published systematic review concluded that the methodological quality of studies evaluating costs of robotic surgery was low and insufficient to inform action by hospitals . For example, cost accounting methods vary regarding the inclusion of capital cost of a robot and other indirect cost, such as administrative salaries, housekeeping, and many other nonrelated variables.…”
Section: Introductionmentioning
confidence: 99%
“…The peer‐reviewed literature has traditionally focused on the cost of robotic surgery by case rather than the CoO of the robot itself . Additionally, when most US hospitals consider the cost of owning the da Vinci robot, they typically assess robotics differently than capital medical equipment used in laparoscopy, such as towers and generators, etc . Why are there so many different cost accounting methods when it comes to assessing robotic vs laparoscopic costs?…”
Section: Introductionmentioning
confidence: 99%